Was Lakatos an epistemic realist? the role of truth in the Methodology of scientific research programs - Borge, Bruno (Faculdade de Filosofia e Ciências, 2021)
A widespread interpretation of Lakatos’ work says his project completely sidestepped the question of truth as a central part of the analysis of scientific knowledge. In a similar vein, Hacking states that Lakatos found in methodology a substitute for truth. Even those who are skeptical of these interpretations agree that Lakatos failed to give an account of the relation between the growth of knowledge and increasing verisimilitude. In this paper I maintain that (a) the problem of truth is central to Lakatos’ philosophical project, and (b) it is possible to develop an alternative interpretation in which his project to establish a link between method and truth can be seen as successful. I put forward a Davidsonian interpretation that ascribes to Lakatos an epistemic realism.